Voice, posture and autonomic nervous system: relations and treatment - Cardoso, Ricardo Manuel Tavares (2020)
Voice is the tool of excellence for verbal communication. For teachers, voice is their main instrument of work, since it allows them to transmit knowledge, thus being of great importance in the teaching-learning process. When used improperly, voice quality can suffer great damages and it can lead to serious health consequences. The theoretical framework of this PhD thesis is comprised of three systematic review articles covering the associations between posture, voice and dysphonia (paper 1), the associations between autonomic nervous system function, voice and dysphonia (paper 2), and the effectiveness of physiotherapy and complementary therapies on voice disorders (paper 3). The thesis also integrates three experimental articles. The first aimed to verify if there were differences in posture, muscle tension and voice between teachers with (n=13) and without (n=11) voice complaints (assessed by photogrammetry, muscle tension through palpation, algometry, aerodynamic assessment of voice, acoustic and auditory-perceptual analysis of voice - paper 4). The second analyzed if there were differences in autonomic nervous system function and voice between teachers with (n=13) and without (n=11) voice complaints (assessed by heart rate variability, The Questionnaire of Autonomic Dysfunction, aerodynamic assessment of voice, acoustic and auditory-perceptual analysis of voice - paper 5). Finally, a randomized controlled trial that was undertaken to verify the effects of myofascial release in teachers’ posture, muscle tension and voice (n=12), compared to a control group (n=12), is presented (assessed by photogrammetry, muscle tension through palpation, algometry, aerodynamic assessment of voice, acoustic and auditory-perceptual analysis of voice - paper 6). With this investigation it was found that in teachers and/or in other samples there is a close relationship between body posture, muscle tension, laryngeal musculature, voice production, voice complaints and dysphonia, as well as autonomic dysfunctions related to voice and dysphonia, where participants with dysphonia tend to present more symptoms of autonomic dysfunction concomitant with activation of the laryngeal musculature (papers 1, 2, 4, 5). It has also been found that myofascial release in teachers, as well as massage, transcutaneous electrical nerve stimulation and acupuncture in other samples, appear to be effective treatments to reduce muscle tension, voice complaints and improve voice quality, supporting the inclusion of these therapies in the treatment of patients with voice disorders, promoting a transdisciplinary action that can optimize assessment and treatment in order to provide benefits to patients with voice problems (papers 3, 6).